Predicted stable Li5P2 and Li4P at ambient pressure: novel high-performance anodes for lithium-ion batteries. Issue 34 (19th August 2020) - Fei, Ge; Duan, Shuai; Zhang, Mingxin; Ren, Zebin; Cui, Yangfan; Chen, Xin; Liu, Yunxian; Yi, Wencai; Liu, Xiaobing
Abstract : Two novel Li–P states as P 3 m 1 Li5 P2 and R 3̄ m Li4 P are predicted to have high battery capacities of 2164 and 3462 mA h g −1, respectively. They can be quenchable down to ambient conditions and are promising candidates for high-performance LIB anode materials. Abstract : Lithium-rich phosphides have recently attracted considerable attention due to their potential application as high-capacity and high-rate anodes for lithium-ion batteries (LIBs). However, there is still short of the promising candidate thus far because of the poor electrical conductivity or huge volume change in the already known Li–P compounds. In this work, we report two novel Li–P states, Li5 P2 and Li4 P, stabilized under high pressures that are predicted to be quenchable down to ambient conditions by first-principles swarm structure calculations. The predicted P 3 m 1 Li5 P2 shows interesting features as a p-type semiconductor with an indirect band gap of 0.787 eV, possessing significant anisotropy properties in electrical transport, while R 3̄ m Li4 P acts as a typical electride with metallic behavior at pressures of 0–82 GPa. More importantly, our calculations reveal that the theoretical capacities of Li5 P2 and Li4 P are predicted to reach 2164 and 3462 mA h g −1, respectively. Combined with the good electrical transport properties, the calculated volume expansion of Li5 P2 (130%) is found to be much smaller than those of the previously reported Li–P compounds, indicating its potential as a high performance anode material for LIBs.